A closed 3D printed microfluidic device for automated growth and differentiation of cerebral organoids from single-cell suspension - Kandra, Mario; Vanova, Tereza; Jongen, Vincent A; Pospíšil, Jakub; Novák, Josef; Chochola, Václav; Buryška, Tomáš; Prokop, Zbyněk; Hodný, Zdeněk; Hampl, Ales; Bohaciakova, Dasa; Jaros, Josef (Biotechnology journal, 2024)
The development of 3D organoids has provided a valuable tool for studying human tissue and organ development in vitro. Cerebral organoids, in particular, offer a unique platform for investigating neural diseases. However, current methods for generating cerebral organoids suffer from limitations such as labor-intensive protocols and high heterogeneity among organoids. To address these challenges, we present a microfluidic device designed to automate and streamline the formation and differentiation of cerebral organoids. The device utilizes microwells with two different shapes to promote the formation of a single aggregate per well and incorporates continuous medium flow for optimal nutrient exchange. In silico simulations supported the effectiveness of the microfluidic chip in replicating cellular microenvironments. Our results demonstrate that the microfluidic chip enables uniform growth of cerebral organoids, significantly reducing the hands-on time required for maintenance. Importantly, the performance of the microfluidic system is comparable to the standard 96-well plate format even when using half the amount of culture medium, and the resulting organoids exhibit substantially developed neuroepithelial buds and cortical structures. This study highlights the potential of custom-designed microfluidic technology in improving the efficiency of cerebral organoid culture.
Keywords: Equipment Design; laboratoř na čipu; Printing, Three-Dimensional; pluripotent stem cells; Lab-On-A-Chip Devices; buněčná diferenciace; lidé; 3D tisk; mozek; tissue engineering; Organoids; 3D cell culture; organoidy; Brain; microfluidics; Cell Differentiation; buněčné kultury; Cell Culture Techniques; design vybavení; organoids; Humans